Regional Variation of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Enterobacterales, Fluoroquinolone-Resistant Salmonella enterica and Methicillin-Resistant Staphylococcus aureus Among Febrile Patients in Sub-Saharan Africa - Moirongo, Rehema Moraa; Lorenz, Eva; Ntinginya, Nyanda E.; Dekker, Denise; Fernandes, José; Held, Jana; Lamshöft, Maike; Schaumburg, Frieder; Mangu, Chacha; Sudi, Lwitiho; Sie, Ali; Souares, Aurelia; et al. (Frontiers in Microbiology, 2020)
Background: Antimicrobial resistance (AMR) thwarts the curative power of drugs and is a present-time global problem. We present data on antimicrobial susceptibility and resistance determinants of bacteria the WHO has highlighted as being key antimicrobial resistance concerns in Africa, to strengthen knowledge of AMR patterns in the region. Methods: Blood, stool and urine specimens of febrile patients, aged between ≥30 days and ≤15 years and hospitalized in Burkina Faso, Gabon, Ghana and Tanzania were cultured from November 2013 to March 2017 (Patients >15 years were included in Tanzania). Antimicrobial susceptibility testing was performed for all Enterobacterales and Staphylococcus aureus isolates using disk diffusion method. Extended-spectrum beta-lactamase (ESBL) production was confirmed by double-disk diffusion test and the detection of blaCTX-M, blaTEM and blaSHV. Multilocus sequence typing was conducted for ESBL-producing Escherichia coli and Klebsiella pneumoniae, ciprofloxacin-resistant Salmonella enterica and S. aureus. Ciprofloxacin-resistant Salmonella enterica were screened for plasmid-mediated resistance genes and mutations in gyrA, gyrB, parC and parE. S. aureus isolates were tested for the presence of mecA and Panton-Valentine Leukocidin (PVL) and further genotyped by spa typing. Results: Among 4,052 specimens from 3,012 patients, 219 cultures were positive of which 88.1% (n=193) were Enterobacterales and 7.3% (n=16) S. aureus. The prevalence of ESBL-producing Enterobacterales (all CTX-M15 genotype) was 45.2% (14/31; 95% CI: 27.3, 64.0) in Burkina Faso, 25.8% ( 8/31; 95% CI: 11.9, 44.6) in Gabon, 15.1% (18/119; 95% CI: 9.2, 22.8) in Ghana and 0.0% (0/12; 95% CI: 0.0, 26.5) in Tanzania. ESBL positive non-typhoid Salmonella (n=3) were detected in Burkina Faso only and methicillin-resistant S. aureus (n=2) were detected in Ghana only. While sequence type (ST)131 predominated among ESBL E. coli (39.1%;9/23), STs among ESBL K. pneumoniae were highly heterogenous. Ciprofloxacin resistant nt Salmonella were commonest in Burkina Faso (50.0%; 6/12) and all harbored qnrB genes. PVL were found in 81.3% S. aureus. Conclusions: Our findings reveal a distinct susceptibility pattern across the various study regions in Africa, with notably high rates of ESBL-producing Enterobacterales and ciprofloxacin-resistant nt Salmonella in Burkina Faso. This highlights the need for local AMR surveillance and reporting of resistances to support appropriate action.